Calibrating a digital camera - Montalvo, R. A. (2021)
The visualization of areas, volumes, topologies and perspectives objects that stay in our environment are making by ours eyes and brain, which have a long evolution through millions years ago. This ensemble between eyes and brain must be simulated by technology in which an artificial intelligence entity take an autonomous decision based on data information acquired by sensors and computer vision. The fidelity of acquired information from the environment is the fundamental key for a good decision. In this context, the cameras and optical lens miniaturization involves distortions which modify the acquired images of areas, volumes, topologies and perspectives objects. In the present work, we make a calibration process of optical cameras which involves radial and tangential distortions, and using OpenCV libraries we calculate the intrinsics and extrinsics parameters which permit us to obtain correct caquired images.